Independent Domination Degree of Standard Graphs of Adriatic \((a,b)\)-KA Indices - Mekala, Anjaneyulu; Kumar, U. Vijaya Chandra; Murali, R. (Communications in Mathematics and Applications, 2023)
The dominating set \(D\) of the graph \(K=(V,E)\) is the independent dominating set (Ids), the independent domination number \(i(K)\) of the graph \(K\) is the minimum cardinality of id. In this article, we introduce the new independent degree domination (idd) of each vertices \(s\in V(K)\), denoted by \(d_{id}(s)\) and compute the Adriatic \((a,b)\)-KA index for book graphs, cycle middle graphs and windmill graphs.
Keywords: Topological index; Adriatic (a,b)-KA index; Independent degree domination; Independent minimal dominating number